Filtered feedback PID control for WirelessHART networked plant - Abdullah, H. (Institute of Electrical and Electronics Engineers Inc., 2017)
The dynamism and portability of wireless installation allows for measurements to be obtained online in such environments hitherto considered challenging for wired measurements. WirelessHART standard has been in the open market for few years already. It has been acknowledged as a viable alternative to wired networks. By deploying wireless sensor network, the cost and period of wiring installation, maintenance and commissioning can be reduced. A Key issue associated with wireless networked control system is the packet dropout. This is prompted by the non-periodic update of measurements as a result of the use of wireless network in the control loop. The packet dropout can cause degradation and declining of the control performance and could possibly jeopardize plant safety. To overcome this phenomenon, this paper presents the application of filtered feedback PID control strategy. Analysis of the results obtained shows that the performance of the plant with the proposed method is better than the conventional PID control. © 2016 IEEE.